2008
DOI: 10.1152/ajpregu.00492.2007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal mitochondrial dysfunction in rat aging

Abstract: Navarro A, Ló pez-Cepero JM, Bá ndez MJ, Sá nchez-Pino M-J, Gó mez C, Cadenas E, Boveris A. Hippocampal mitochondrial dysfunction in rat aging. Am J Physiol Regul Integr Comp Physiol 294: R501-R509, 2008. First published December 12, 2007 doi:10.1152/ajpregu.00492.2007.-Hippocampus mitochondrial dysfunction with impaired electron transfer and increased oxidative damage was observed upon rat aging. Hippocampal mitochondria of aged (12 mo) and senescent (20 mo) rats showed, compared with young (4 mo) rats, mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
80
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 46 publications
8
80
1
2
Order By: Relevance
“…This brain area depends considerably on mitochondrial functionality as documented by the large number of papers describing agerelated mitochondrial dysfunctions such as decreased rate of electron transfer in complex I and complex IV, decreased membrane potential, and increased content of macromolecular oxidized products (Bagh et al 2011;Frenzel et al 2010;Gilmer et al 2010;Guevara et al 2009Guevara et al , 2011Navarro and Boveris 2010;Navarro et al 2008). In this brain area, we found that AL rats presented an age-related increase in TFAM amount, which was not associated with an increase in mtDNA content, but with a mtDNA decrease.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This brain area depends considerably on mitochondrial functionality as documented by the large number of papers describing agerelated mitochondrial dysfunctions such as decreased rate of electron transfer in complex I and complex IV, decreased membrane potential, and increased content of macromolecular oxidized products (Bagh et al 2011;Frenzel et al 2010;Gilmer et al 2010;Guevara et al 2009Guevara et al , 2011Navarro and Boveris 2010;Navarro et al 2008). In this brain area, we found that AL rats presented an age-related increase in TFAM amount, which was not associated with an increase in mtDNA content, but with a mtDNA decrease.…”
Section: Discussionmentioning
confidence: 60%
“…Here, we decided to measure not only TFAM amount and mtDNA content, but also the in vivo binding activity of TFAM in rat frontal cortex, one among the brain areas mostly affected by the age-related mitochondrial dysfunction (Navarro et al 2008;Navarro and Boveris 2010). In aged AL rats, we found age-related increased amount of TFAM, loss of mtDNA content, increased content of the 4.8-kb deletion, and decreased TFAM binding to mtDNA.…”
mentioning
confidence: 99%
“…Disfunções mitocondriais são caracterizadas pela redução do controle respiratório, diminuição no potencial de membrana e desacoplamento mitocondrial (15) . Essas alterações são observadas no envelhecimento e em situações patológicas (5,15) .…”
Section: Discussionunclassified
“…Essas alterações são observadas no envelhecimento e em situações patológicas (5,15) . Prejuízos na atividade do complexo IV, por exemplo, estão relacionados com a doença de Alzheimer (16) e do complexo I, com Parkinson (17) .…”
Section: Discussionunclassified
“…There is an ongoing debate concerning the magnitude of decline in mitochondrial respiration that occurs during normal aging (Gilmer et al, 2010). Some groups report extensive age-related declines in mitochondrial respiration (Chiu and Richardson, 1980;Cocco et al, 2005;Navarro et al, 2005Navarro et al, , 2008Petrosillo et al, 2008a,b). Our laboratory and others (Bustamante et al, 2008;Deshmukh et al, 1980;Gilmer et al, 2010;Leslie et al, 1985;Meng et al, 2007) previously reported no significant age-related changes in cortical mitochondrial bioenergetics in naïve rats, while significant elevations in oxidative damage were apparent (Gilmer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%